Pengembangan Media Evaluasi Pembelajaran IPS â€œMAPSâ€ dengan Game Web Browser Based Learning untuk siswa SMP - Eko Putro, Santi Dwi Retno; Adi, Khofifatu Rohmah; Ratnawati, Nurul (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2021)
Purpose of this research is to produce Social Studies Learning Evaluation Media â€œMAPSâ€. This media is designed with a web browser-based learning game for junior high school students, testing their feasibility and practicality. This study adopts seven stages of research and development by Borg and Gall: (1) Analysis of potentials and problems, (2) data collection, (3) product design, (4) design validation, (5) design revisions, (6) product trials, (7) final product revisions. The subjects of this study are social studies teacher and 31 students VII.6 students of State Junior High School 23 Malang with data collection instruments in the form of questionnaires. The feasibility test results that have been conducted, show an average score of 3.71 for material validation, 3.5 for validation of IPS learning evaluation, and 3.87 for media validation. Based on the average value, social studies learning evaluation media "MAPS" is declared "Very Feasible" to use. The media practicality test was conducted based on the response of the test subject. Practicality test results showed a percentage of 97.5% for teacher responseÂ results and 87.66% for student response results. Based on the percentage of user response, social studies learning evaluation media "MAPS" can be declared "Very Practical" to use.